Organic phosphine flame-retardant nylon composition with excellent wet electrical property as well as preparation method and application of organic phosphine flame-retardant nylon composition

By adding specific types of nylon resin, glass fiber and inorganic synergist to the nylon composition, the component ratio and glass transition temperature are optimized, and the problem of degradation of organic phosphine flame-retardant nylon in wet environments is solved, and the unity of high flame retardant performance, excellent wet electrical performance and high mechanical properties is achieved, and it is suitable for the new energy industry.

CN119823568AActive Publication Date: 2025-04-15KINGFA SCI & TECH CO LTD

Patent Information

Application Number
CN202411914799.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-15
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Organic phosphine flame-retardant nylon has deteriorated electrical performance in wet environments, and its electrical performance is poor after high temperature and high humidity treatment in the new energy industry, which limits its application.

Method used

By adding long-carbon chain aliphatic nylon resin, semi-aromatic nylon resin, hydrolyzed glass fiber and inorganic synergist to the nylon composition, the glass transition temperature and component ratio of the nylon resin are optimized, the water absorption rate and water absorption rate are reduced, and the wet electrical properties are improved.

Benefits of technology

It has achieved excellent wet electrical properties of organic phosphine flame-retardant nylon composition under high temperature and high humidity conditions, and has high flame-retardant performance and mechanical properties, meeting the application needs of the new energy industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206583560000061
    Figure BDA0005206583560000061
  • Figure BDA0005206583560000071
    Figure BDA0005206583560000071
  • Figure FDA0005206583550000011
    Figure FDA0005206583550000011
Patent Text Reader

Abstract

The invention discloses an organic phosphine flame-retardant nylon composition with excellent wet electrical properties as well as a preparation method and application of the organic phosphine flame-retardant nylon composition. The organic phosphine flame-retardant nylon composition comprises the following components in parts by weight: 23-53 parts of short carbon chain aliphatic nylon resin, 10-15 parts of long carbon chain aliphatic nylon resin, 5-10 parts of semi-aromatic nylon resin, 20-30 parts of glass fibers, 10-16 parts of hypophosphite and 2-6 parts of an inorganic synergist, the glass transition temperature of the semi-aromatic nylon resin is greater than or equal to 88 DEG C, and the glass transition temperature of the long carbon chain aliphatic nylon resin is greater than or equal to 90 DEG C. The glass fibers are hydrolysis-resistant glass fibers. The organic phosphine flame-retardant nylon composition disclosed by the invention can realize the unification of high flame-retardant property and high-wet-state electrical property, and has high mechanical property at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to an organic phosphine flame-retardant nylon composition with excellent wet electrical properties, a preparation method and application thereof. Background Art

[0002] Organophosphine flame retardant nylon has excellent flame retardant properties, mechanical properties, low smoke and halogen-free, and environmental protection, and is widely used in electronic appliances, new energy, rail transportation and other fields. Nylon has excellent electrical properties in a dry state, but it is very easy to absorb water in a wet environment. After absorbing water, the electrical properties of nylon will drop significantly, and the introduction of organophosphine flame retardants will further deteriorate the wet electrical properties of nylon.

[0003] In the new energy industry, materials are often required to have excellent electrical properties after high temperature and high humidity treatment (treated at 85°C and 85% RH for 1008h). However, due to its low wet electrical properties, organic phosphine flame retardant nylon has severely limited its application in the new energy industry. Therefore, it is urgent to develop an organic phosphine flame retardant nylon composition that can take into account both high flame retardant properties and wet electrical properties, and can also maintain excellent mechanical properties, so as to meet the application needs of materials in the new energy industry. Summary of the invention

[0004] In view of the defects in the prior art, the present invention provides an organic phosphine flame-retardant nylon composition with excellent wet electrical properties, a preparation method and application thereof.

[0005] The invention provides an organic phosphine flame retardant nylon composition, which comprises the following components by weight: 23-53 parts of a short carbon chain aliphatic nylon resin, such as 23, 25, 30, 35, 40, 45, 50, 53 parts; 10-15 parts of a long carbon chain aliphatic nylon resin, such as 10, 11, 12, 13, 14, 15 parts; 5-10 parts of a semi-aromatic nylon resin, such as 5, 6, 7, 8, 9, 10 parts; 20-30 parts of glass fiber, such as 20, 22, 24, 26, 28, 30 parts; 10-16 parts of hypophosphite, such as 10, 11, 12, 13, 14, 15, 16 parts; and 2-6 parts of an inorganic synergist, such as 2, 3, 4, 5, 6 parts; wherein the mass percentage of the nylon resin in the composition is not less than 48%.

[0006] The glass transition temperature of the semi-aromatic nylon resin is ≥88°C, preferably 90-130°C, and the glass transition temperature is tested using a differential scanning calorimeter according to ISO 11357-3:2013. The inventors have found that the glass transition temperature of the semi-aromatic nylon resin is ≥88°C, which can promote the barrier effect of the nylon composition under high temperature and high humidity conditions, and promote carbonization to further improve the flame retardant performance;

[0007] The glass fiber is a hydrolysis-resistant glass fiber, which can inhibit the hydrolysis of nylon molecular chains under high temperature and high humidity, thereby improving the wet electrical properties of the composition;

[0008] The use of an inorganic synergist as a flame retardant synergist in the system of the present invention has the advantages of good stability and the ability to inhibit the decomposition of nylon molecular chains.

[0009] The present invention reduces the water absorption rate and water absorption ratio of nylon molecular chains through the dual synergy of the low hygroscopicity of long-carbon-chain aliphatic nylon resin and the barrier property of semi-aromatic nylon resin, thereby improving the wet electrical properties of organic phosphine flame-retardant nylon; by limiting the content of semi-aromatic nylon resin and long-carbon-chain aliphatic nylon resin, the wet electrical properties of the organic phosphine flame-retardant nylon composition are significantly improved while still maintaining good flame retardant properties and mechanical properties; at the same time, by specially selecting the glass transition temperature of the semi-aromatic nylon resin, the flame retardant properties and mechanical properties are improved while the wet electrical properties are further improved, thereby achieving the unification of comprehensive properties; by selecting hydrolysis-resistant glass fiber and flame retardant synergist, the hydrolysis of nylon molecular chains under high temperature and high humidity conditions can be reduced, thereby improving the wet electrical properties of organic phosphine flame-retardant nylon.

[0010] Furthermore, the short carbon chain aliphatic nylon resin is a combination of one or more of PA66, PA6, PA56, and PA66 / 6.

[0011] Furthermore, the long carbon chain aliphatic nylon resin is one or more of PA610, PA612 or PA1010; the melting point of the long carbon chain aliphatic nylon resin is ≥200°C, preferably 200-230°C, and the melting point is tested using a differential scanning calorimeter according to ISO 11357-3:2011 standard.

[0012] Furthermore, the semi-aromatic nylon resin is one or more of PA6T / 66, PA6I / 6T or PA6T / M-5T, and the PA6T / 66 has a 6T content of 54-65%.

[0013] Furthermore, the hydrolysis-resistant glass fiber is E glass fiber, preferably E glass fiber surface-modified by a silane coupling agent.

[0014] Furthermore, the inorganic synergist is any one or more of boehmite or polyaluminium phosphite;

[0015] Furthermore, the nylon composition further comprises 0.1-1 parts by weight of an antioxidant and / or 0.1-1 parts by weight of a lubricant, and may further comprise other additives.

[0016] Furthermore, the hypophosphite is one or more of aluminum hypophosphite, diethyl aluminum hypophosphite, and diisopropyl aluminum hypophosphite, preferably diethyl aluminum hypophosphite.

[0017] The present invention also provides a method for preparing the nylon composition, comprising the following steps:

[0018] Weighing each component by weight, putting each component into a mixer to mix until uniform, to obtain a premix, and then putting the obtained premix into a twin-screw extruder for melt mixing, and extruding and granulating to obtain the nylon composition;

[0019] The twin-screw extruder has a screw speed of 250-350 rpm, an aspect ratio of (40-48):1, and a barrel temperature of 200-290°C.

[0020] The present invention also provides application of the nylon composition in high-voltage connectors and new energy batteries.

[0021] In summary, compared with the prior art, the present invention achieves the following technical effects:

[0022] (1) The nylon composition provided by the present invention has excellent mechanical properties;

[0023] (2) The nylon composition provided by the present invention can maintain excellent wet electrical properties while taking into account high flame retardancy. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0025] Example

[0026] The present invention is further described below in conjunction with specific examples and comparative examples. The following specific examples are all preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the following examples, and are particularly not limited to the types of the various component raw materials used in the following specific examples.

[0027] 1. The sources of raw materials for the embodiments and comparative examples are as follows:

[0028] Short carbon chain aliphatic nylon resin #1: PA66, grade PA66 EP-158, Huafeng Group;

[0029] Short carbon chain aliphatic nylon resin #2: PA6, brand PA6 HY-2800A, Haiyang Chemical Fiber Company;

[0030] Long carbon chain aliphatic nylon resin #1: PA612, brand PA612 A120, melting point 215°C, Shandong Guangyin New Materials Co., Ltd.;

[0031] Long carbon chain aliphatic nylon resin #2: PA610, brand PA610 F120, melting point 222°C, Shandong Guangyin New Materials Co., Ltd.;

[0032] Long carbon chain aliphatic nylon resin #3: PA1212, brand PA1212, melting point 184°C, Shandong Dongchen Ruisen New Material Technology Co., Ltd.;

[0033] Semi-aromatic nylon resin #1: PA6I / 6T, brand TI1207, glass transition temperature 130°C, Shandong Guangyin New Materials Co., Ltd.;

[0034] Semi-aromatic nylon resin #2: PA6T / 66, 6T content of 55%, brand VicnyI 400PNC003, glass transition temperature 95°C, Zhuhai Wantong Special Engineering Plastics Co., Ltd.

[0035] Semi-aromatic nylon resin #3: PA6T / M-5T, brand name PA6T / M-5T, glass transition temperature 135°C, DuPont, USA;

[0036] Semi-aromatic nylon resin #4: PA66 / 6T, 6T content of 25%, brand NPD-652, glass transition temperature of 70°C, INVISTA Co., Ltd.

[0037] Hypophosphite: diethylaluminum hypophosphite, brand OP1230, Klein Co., Ltd.;

[0038] Inorganic synergist #1: boehmite, brand BG-613SO, Anhui Yishitong Materials Technology Co., Ltd.;

[0039] Inorganic synergist #2: polyaluminium phosphite, brand PA2103, Shenzhen Ruishixing Technology Co., Ltd.;

[0040] Flame retardant synergist #3: melamine polyphosphate, brand BUDIT 3141, purchased from Budenheim Iberica, Germany;

[0041] Glass fiber #1: E glass fiber, brand ECS10-3.0-568H, surface modifier is silane coupling agent, China Jushi Co., Ltd.;

[0042] Glass fiber #2: TLD glass fiber, brand TLD-CS10-3.0-T436S, surface modifier is silane coupling agent, Taishan Glass Fiber Co., Ltd.;

[0043] Antioxidant: Brand RIANOX 1098, the same substance was used in parallel tests;

[0044] Lubricant: Brand A-C540A, the same material was used in parallel tests.

[0045] The preparation method of the polyamide / polyolefin composite material of the embodiment of the present invention and the comparative example comprises the following steps:

[0046] Weighing each component by weight, putting each component into a mixer to mix until uniform, to obtain a premix, and then putting the obtained premix into a twin-screw extruder for melt mixing, and extruding and granulating to obtain the nylon composition;

[0047] The twin-screw extruder has a screw speed of 250-350 rpm, an aspect ratio of (40-48):1, and a barrel temperature of 200-290°C.

[0048] 2. Various performance test methods

[0049] (1) Flame retardant performance: The flame retardant performance of the sample strip is tested according to the relevant standards of UL 94-2015. The sample thickness is 0.8 mm. The flame retardant grades are divided into V-0, V-1, V-2 and no grade (NR). Flame retardant performance is of great significance to electrical safety. The UL94 flame retardant grade needs to reach V-0 to meet application requirements;

[0050] (2) Tensile strength: tested in accordance with ISO 527-2012;

[0051] (3) Wet electrical properties test: To test the insulation resistance, the square plate (sample size: 100*100*1mm) was first treated under double 85 conditions (85℃ / 85%RH) for 1008h, left for 4h, and the surface moisture was wiped dry. The test was performed in accordance with IEC 62631-3-3-2015, with a test voltage of 1000V DC and a pressure application time of 1min.

[0052] Table 1 Technical solutions and effects of the embodiments (unit: weight parts)

[0053]

[0054] Table 2 Comparative Example Technical Scheme and Effects (Unit: Weight Parts) Comparative Example 4

[0055]

[0056] In Examples 1-9, short carbon chain aliphatic nylon resin, long carbon chain aliphatic nylon resin, semi-aromatic nylon resin with a specific glass transition temperature, specific flame retardant synergist and glass fiber are introduced at the same time. Through the combination of formulas, the organic phosphorus flame retardant nylon composition has high wet electrical properties and high mechanical properties while obtaining high flame retardant properties. Among them, the vertical combustion performance of the nylon composition has reached V-2 level or above, basically reaching V-0 level, and the tensile strength has reached 108MPa or above, basically reaching 120MPa or above. At the same time, after the composition is treated under high temperature and high humidity conditions, the insulation resistance remains above 23GΩ, with excellent wet electrical properties, achieving the unity of high flame retardant properties and wet electrical properties of the organic phosphorus nylon composition.

[0057] Comparative Examples 1-7 are all compared with Example 3. Comparative Example 1 only adds conventional short-chain aliphatic nylon resin, and is not compounded with long-chain aliphatic nylon resin and semi-aromatic nylon resin. From the test data, it can be seen that the conventional organic phosphine flame retardant nylon resin has poor wet electrical properties; the amount of long-chain aliphatic nylon resin added in Comparative Example 3 is too small, and it cannot play a good role in reducing the water absorption rate in the system, so that the wet electrical properties of the nylon composition are significantly reduced; the amount of semi-aromatic nylon resin added in Comparative Example 3 is too small, and it cannot play a good role in reducing the water absorption rate and limiting ion mobility in the system, so that the organic phosphine flame retardant nylon composition has poor flame retardant properties and wet electrical properties; Comparative Example 4 adds too much semi-aromatic nylon resin, so that the organic phosphine flame retardant nylon composition has poor compatibility, resulting in a decline in mechanical properties and wet electrical properties; the semi-aromatic nylon resin used in Comparative Example 5 The glass transition temperature of nylon resin is lower than 90°C, so that the semi-aromatic nylon resin cannot play a good barrier role under high heat and high humidity conditions, and the carbonization is also relatively poor, which reduces the flame retardant properties and wet electrical properties of the nylon composition; the glass fiber used in comparative example 6 is not hydrolysis-resistant glass fiber, so that under high temperature and high humidity conditions, the glass fiber cannot well inhibit the hydrolysis of the nylon molecular chain, thereby reducing the wet electrical properties of the organic phosphine flame retardant nylon composition; comparative example 7 uses melamine phosphate as a flame retardant synergist. Although it can give the organic phosphine flame retardant nylon composition good flame retardant properties and mechanical properties, it will seriously deteriorate its wet electrical properties. This is because melamine polyphosphate has poor thermal stability and is easily degraded to produce phosphoric acid, which further promotes the degradation of the nylon molecular chain under high temperature and high humidity conditions, resulting in poor wet electrical properties of the organic phosphine flame retardant nylon composition. The above comparative examples cannot achieve high flame retardant properties while taking into account wet electrical properties and good mechanical properties.

[0058] Based on the test data of vertical combustion performance, tensile strength and insulation resistance in Table 1 and Table 2, the organic phosphine flame retardant nylon composition prepared by Examples 1-9 has obvious advantages over the comparative example and can effectively meet the high standards of customers and the market.

[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An organic phosphine flame retardant nylon composition, comprising the following components in parts by weight: The glass transition temperature of the semi-aromatic nylon resin is ≥88°C; The glass fiber is hydrolysis-resistant glass fiber.

2. The nylon composition according to claim 1, characterized in that The short carbon chain aliphatic nylon resin is one or more of PA66, PA6, PA56 and PA66 / 6.

3. The nylon composition according to claim 1, characterized in that The long carbon chain aliphatic nylon resin is one or more of PA610, PA612 or PA1010; Preferably, the melting point of the long carbon chain aliphatic nylon resin is ≥ 200°C.

4. The nylon composition according to claim 1, characterized in that The semi-aromatic nylon resin is one or more of PA6T / 66, PA6I / 6T or PA6T / M-5T.

5. The nylon composition according to claim 1, characterized in that The hydrolysis-resistant glass fiber is E glass fiber, preferably E glass fiber surface-modified by a silane coupling agent.

6. The nylon composition according to claim 1, characterized in that The inorganic synergist is any one or more of boehmite or polyaluminium phosphite.

7. The nylon composition according to claim 1, characterized in that The hypophosphite is one or more of aluminum hypophosphite, diethyl aluminum hypophosphite, and diisopropyl aluminum hypophosphite.

8. The nylon composition according to claim 1, characterized in that The glass transition temperature of the semi-aromatic nylon resin is 90-130°C.

9. The method for preparing the nylon composition according to any one of claims 1 to 8, characterized in that: The steps include: The components are weighed in parts by weight, and the components are put into a mixer to be mixed until uniform to obtain a premix, and then the obtained premix is ​​put into a twin-screw extruder for melt mixing, and extrusion granulation is performed to obtain the nylon composition.

10. Use of the nylon composition according to any one of claims 1 to 8 in high-voltage connectors and new energy batteries.

Citation Information

Patent Citations

  • Poly / mono-phosphorous acid condensed diphosphite compound as well as preparation and application thereof

    CN112093786A

  • High-voltage-breakdown-resistant and flame-retardant reinforced nylon material and preparation method thereof

    CN114836032A

Cited By

  • Nylon-SPS composition as well as preparation method and application thereof

    CN122060317A

  • Organic phosphine flame-retardant nylon composition having good wet electrical properties, and preparation method therefor and use thereof

    WO2026138316A1